1993
DOI: 10.1073/pnas.90.1.317
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione ester delays the onset of scurvy in ascorbate-deficient guinea pigs.

Abstract: Previous studies showed that administration of ascorbate to glutathione (GSH)-deflcient newborn rats and guinea pigs prevented toxicity and mortality and led to increased tissue and mitochondrial GSH levels; ascorbate thus spares GSH. In recent work it was shown that glutathione (GSH) deficiency in newborn rats (1-4, 30) and in guinea pigs (5), produced by administration of buthionine sulfoximine [a transition-state inhibitor of y-glutamylcysteine synthetase (6-8)], leads to death within a few days. In newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…In vivo animal studies have provided evidence for a coupling between the cellular levels of glutathione and vitamin C. In animals depleted of glutathione by treatment with buthionine sulfoximine, supplementation with vitamin C protected cells from oxidative damage (11). In addition, in scorbutic animals, supplementation with precursors of glutathione such as glutathione methyl ester protected the animals from early death (46). There is, however, no direct evidence indicating a relationship between the differential capacity of cells to accumulate ascorbic acid and their respective intracellular concentrations of glutathione.…”
Section: Infection With Hiv-1 Induces Increased Transport and Accumulmentioning
confidence: 82%
“…In vivo animal studies have provided evidence for a coupling between the cellular levels of glutathione and vitamin C. In animals depleted of glutathione by treatment with buthionine sulfoximine, supplementation with vitamin C protected cells from oxidative damage (11). In addition, in scorbutic animals, supplementation with precursors of glutathione such as glutathione methyl ester protected the animals from early death (46). There is, however, no direct evidence indicating a relationship between the differential capacity of cells to accumulate ascorbic acid and their respective intracellular concentrations of glutathione.…”
Section: Infection With Hiv-1 Induces Increased Transport and Accumulmentioning
confidence: 82%
“…To our surprise, the administration of ascorbic acid, another hydrophilic antioxidant, by an identical regimen failed to exert significant protection in this ischemic reperfusion model. Previous studies have demonstrated that GSH and ascorbic acid have many actions in common and that they can compensate for each other under conditions where one of them is systemically depleted (Martensson et al, 1991(Martensson et al, , 1993Meister, 1994). However, our present data argue against GSH and ascorbic acid playing equally important roles in myocardial ischemia and reperfusion, a pathological condition where both GSH and ascorbic acid have been reduced locally in ischemic reperfused tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In newborn rats with GSH depletion [by treatment with L-buthionine-(S,R)-sulfoximine], administration of ascorbic acid prevented tissue injury and death (Martensson et al, 1991). On the other hand, in guinea pigs depleted of ascorbic acid (by giving an ascorbic acid-deficient diet), supplementation of GSH ester significantly delayed the onset of scurvy and attenuated tissue injury in these animals (Martensson et al, 1993). These results indicated that GSH and ascorbic acid can compensate for each other under experimental conditions in which one of them is selectively depleted.…”
mentioning
confidence: 99%
“…Ascorbic acid may be a useful tool in recycling α-tochoferol and glutatione radical back to the reduced form as an electron donor in CNS, playing an indirect protective action 27 . Moreover, recent studies have demonstrated that the ascorbic acid is beneficial against peroxynitrite (ONOO-) radical attack, which is closely related to motor neuron damage 28,29 .…”
Section: Discussionmentioning
confidence: 99%